PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA ANGGARAN DI KABUPATEN SEMARANG - Handayani, Bestari Dwi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2011)
The relationship between budget participation and managerial performance has been attracting researcher's attention. However, the results of previous studies on the realtionship between budget participation and managerial performance have been inconclusive and often contradictory. One way to reconcile these conflicting results is to investigate the hypothesized realationship by applying a contingency approach. This study empirically examined the effect of budget participation on budget performance using conntingency approach. Three contingent variables were investigated. They were motivation, leadership style and decentralization. The data were collected by using purposive sampling technique atSemarangRegion. The respondent is the managerial level such as Camat and Bendahara Kecamatan. To analyse the data, simple regresion and regresion with residual approach are employed. The result of study shows that budget participation support has positive and significant influence on performance budgeting. Then, motivation and budget participation, leadership style and budget participation, desentralization and budget participation do not affect performace budgeting.